A systematic review of the literature on code-switching and a discussion on future directions - Mohammed Albahoth, Zakria; Abdul Jabar, Mohd Azidan; Mohd Jalis, Farhana Muslim (Human Resources Management Academic Research Society (HRMARS), 2024)
The study of code-switching holds immense importance in understanding the intricate dynamics of language use and communication in diverse communities, thereby it illuminates how individuals navigate between languages to express identity, convey meaning, and negotiate social relationships. This study investigates code-switching's impact on personality traits among foreigners in Gulf Cooperation Council (GCC) countries, with a focus on Saudi Arabia. Despite a growing body of literature, we applied a systematic literature review approach utilizing the Scopus database, this study analyzed 15 papers to provide a detailed examination of the current landscape of code-switching research across disciplines such as social sciences, linguistics, and cross-cultural communication. We examined and found that the code-switching is a multifaceted phenomenon influenced by social, cultural, and contextual factors. and it serves pragmatic functions and reflects linguistic adaptability. However, its impact on language development and social dynamics varies. The current study emphasizes the need for further research to clarify theoretical foundations, define codeswitching, and explore its role in multicultural environments. The implications of this study suggest a critical need for continued research to enhance our understanding of codeswitching's impact on personality traits, especially among foreigners in GCC countries.